The use of various technologies in the surgical treatment of decompensated forms of varicose veins of the lower extremities with unilateral valvular incompetence of the great saphenous and anterior accessory saphenous vein - O. V. Sokolov (Сучасні медичні технології)
Purpose of the study. Comparative evaluation of the results of treatment of patients with varicose veins (VVs) in stage C6, with the valve incompetence of the trunks of GSV and ASSV in one lower limb, by traditional venectomy and radiofrequency ablation (RFA).